Evidence for Introgression Among Three Species of the Anastrepha fraterculus Group, a Radiating Species Complex of Fruit Flies - Díaz, Fernando; Luís A. Lima, André; Nakamura, Aline M.; Fernandes, Fernanda; Sobrinho, Iderval; de Brito, Reinaldo A. (Frontiers in Genetics, 2018)
Introgression should no longer be considered as rare a phenomenon as once thought, since several studies have recently documented gene flow between closely related and radiating species. Here, we investigated evolutionary relationships among three closely related species of fruit flies of the Anastrepha fraterculus group (Anastrepha fraterculus, A. obliqua and A. sororcula). We sequenced a set of 20 genes and implemented a combined populational and phylogenetic inference with a model selection approach by an ABC framework in order to elucidate the demographic history of these species. The phylogenetic histories inferred from most genes showed a great deal of discordance and substantial shared polymorphic variation. The analysis of several population and speciation models reveal that this shared variation is better explained by introgression rather than convergence by parallel mutation or incomplete lineage sorting. Our results consistently showed these species evolving under an isolation with migration model experiencing a continuous and asymmetrical pattern of gene flow involving all species pairs, even though still showed a more closely related relationship between A. fraterculus and A. sororcula when compared with A. obliqua. This suggests that these species have been exchanging genes since they split from their common ancestor ~2.6 MYA ago. We also found strong evidence for recent population expansion that appears to be consequence of anthropic activities affecting host crops of fruit flies. These findings point that the introgression here found may have been driven by genetic drift and not necessary by selection, which has implications for tracking and managing fruit flies.